Economic volatility in childhood and subsequent adolescent mental health problems: a longitudinal population-based study of adolescents. Issue 9 (18th September 2017) - Bøe, Tormod; Skogen, Jens Christoffer; Sivertsen, Børge; Hysing, Mari; Petrie, Keith J; Dearing, Eric; Zachrisson, Henrik Daae
Abstract : Objective: The aim of the current paper was to investigate the association between the patterns of duration, timing and sequencing of exposure to low family income during childhood, and symptoms of mental health problems in adolescence. Setting: Survey administered to a large population-based sample of Norwegian adolescents. Participants: Survey data from 9154 participants of 16–19 years age (53% participation rate; 52.7% girls) were linked to registry-based information about childhood family income from tax return data. Outcome measures: Mental health outcomes were symptoms of emotional, conduct, hyperactivity, peer problems and general mental health problems measured with the Strengths and Difficulties Questionnaire, symptoms of depression measured with Short Mood and Feelings Questionnaire and symptoms of attention-deficit/hyperactivity disorder (ADHD) measured with the Adult ADHD Self-Report Scale. Results: Latent class analysis and the BCH approach in Mplus were used to examine associations between patterns of poverty exposure and mental health outcomes. Four latent classes of poverty exposure emerged from the analysis. Participants moving into poverty (2.3%), out of poverty (3.5%) or those chronically poor (3.1%) had more symptoms of mental health problems (Cohen's d =16-.50) than those with no poverty exposure (91.1%). This pattern was, however, not found for symptoms of ADHD. The pattern of results was confirmed in robustness checks using observed data. Conclusions: Exposure to poverty in childhood was found to be associated with most mental health problems in adolescence. There was no strong suggestion of any timing or sequencing effects in the patterns of associations.